Regional Variations in US Grocery Prices: Causes and Consumer Responses - Faniyi, Anike Olufisayo (International Journal of Scientific Research and Management (IJSRM), 2024)
This research article provides an in-depth analysis of the regional differences in grocery prices across the United States and examines how these variations influence consumer behavior. The study identifies and evaluates several key factors contributing to price discrepancies, including supply chain issues, local economic conditions, and the level of competition among retailers. By utilizing a combination of quantitative price data from national and local grocery retailers and qualitative insights from consumer surveys, the research offers a comprehensive understanding of the underlying causes of regional price variations.Significant findings reveal that regions with frequent supply chain disruptions, such as the West Coast, often experience higher grocery prices due to logistical challenges and increased transportation costs. Conversely, areas with robust retail competition, like the Midwest, benefit from lower prices driven by competitive market forces. Local economic conditions also play a crucial role, with economically depressed regions seeing higher prices as stores compensate for lower sales volumes.The study further explores how consumers adapt their shopping habits in response to these regional price differences. It highlights the growing reliance on digital tools and apps for price comparisons, especiallkly in high-cost areas. Consumers also tend to shift towards discount stores and bulk purchasing to manage their grocery budgets. In regions with higher grocery prices, there is a noticeable trend towards purchasing from local farmers' markets and co-operatives, which offer fresh produce at competitive prices. Additionally, some consumers adjust their dietary choices to focus on more affordable food items, such as reducing meat consumption and increasing the intake of staple foods.This research underscores the complexity of regional grocery pricing and its significant impact on consumer behavior. By understanding these dynamics, policymakers can develop strategies to improve supply chain efficiency, foster retail competition, and support local markets, ultimately ensuring more equitable access to affordable groceries across the United States.